Mycobiota and mycotoxins in Portuguese pork, goat and sheep dry-cured hams - Rodrigues, Paula (2018)
The objectives of the present work were to survey, for the first time, the contamination of Portuguese fresh and dry-cured meat products with ochratoxin A (OTA) and aflatoxin B1 (AFB1), and to determine the fungi potentially responsible for this contamination. A total of 128 samples including pork fresh legs, dry-cured legs and shoulders, as well as goat and sheep dry-cured legs were analysed. Mycological analysis of these samples yielded a total of 630 fungal isolates. Penicillium sp. was the dominant fungal genus in all products (66% of all isolates). Penicillium nordicum and Aspergillus westerdijkiae were only rarely isolated from pork ham samples. In fresh pork meat, 40% of the samples were contaminated with OTA at levels below 1 μg/kg. In pork dry-cured legs with 20 to 25 months of ripening, 43% of the samples showed detectable contamination, while 18% of the shoulder hams were contaminated. OTA was not detected in any of the goat and sheep samples. OTA contamination does not seem to be a risk in small-piece and short-ripe products like goat and sheep legs, but affects longer ripe products like pork legs and shoulders. Although aflatoxigenic fungi were identified, AFB1 was not detected in any sample, and it should not be considered a risk in dry-cured hams.